Technology Adoption Propensity Among Hungarian Business Students - Laszlo Berenyi; Nikolett Deutsch; Eva Pinter; Peter Bago; Viktor Nagy-Borsy (European Scientific Journal, ESJ, 2021)
The emerging role of technology raises several management challenges. Beyond the ability to develop new tools and solutions, achieving the business goals on new technologies require capable users on the other side. Understanding the factors of technology acceptance has been appreciated in recent decades. The paper aims to explore the approach to technology by using the adoption propensity (TAP) index among Hungarian business students. Gender, study level, and work experience were applied as grouping factors. A voluntary online survey was used for data collection. Based on 345 responses, the results are engaging and progressive. Many of the students have an optimistic approach to new technologies, and a significant part of them shows higher than medium-level proficiency. Parallelly, fear from vulnerability is remarkable among the respondents, which suggests cautious behavior. Gender and study level show significant differences within the sample, but no difference is found based on work experience. The results can be used to evaluate technology adoption readiness or generally support action research in developing industrial technologies.